PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Caroline Silalahi, Sasta; Grace Simalango, Ansari; Giovanni Samosir, Yulia; Sinurat, Franty (EDUTECH CONSULTANT, 2019)
The purpose of this paper is to find out and describe the influence of motivation on employee performance at PT Perkebunan Nusantara III (Persero) Medan. Data collection methods used are field studies (observations and questionnaires), and literature studies. The types of data sources used are primary data and secondary data. The data analysis technique used is descriptive analysis techniques. From the results of the analysis, it can be seen that the influence of motivation on employee performance at PT Perkebunan Nusantara III (Persero) Medan has provided good motivation to employees where part of Abraham Maslow's theory is fulfilling physiological needs, security, social, appreciation and self-actualization needs are met and the application of motivation has shown that improving employee performance is influenced by motivation, which has a high relationship